EU Consumers, Renewable Energy, and Sustainable Development - Veghes, Călin; Strâmbu-Dima, Andreea; Stoenică, Laurentiu (European Journal of Sustainable Development, 2024)
The European Union countries are working to reach the truly ambitious objective of achieving a climate-neutral continent by 2050. Increasing the employment of renewable energy is one of the strategic directions promoted to fulfill this purpose. Although the socioeconomic and political context has accelerated the use of renewable energy sources, shifting to green energy raises significant challenges and generates a substantial impact both at the macroeconomic and microeconomic levels, with particular attention given to the overall behavior of the EU consumers within this transitional process. The paper presents the results of an exploratory approach aiming to assess, based on the secondary data and from a market-oriented perspective, the relationships between the production, consumption, and share of renewable energy, the attitude of EU consumers toward renewable energy and the extent to which they are willing to consider it as a reliable alternative to the traditional energy, in connection to the economic, social, and environmental dimensions of the sustainable development in the EU Member States. Keywords: Renewable energy, EU consumers, Marketing, Sustainable development